Answer:
a) R1 ∪ R2={(1, 1), (1, 2), (2, 1), (2, 2), (2, 3), (3, 1), (3, 2), (3, 3), (3, 4)}
b) R1 ∩ R2= {(1, 2), (2, 3), (3, 4)}
c) R1 – R2= ∅
d) R2 – R1= {(1, 1), (2, 1), (2, 2), (3, 1), (3, 2), (3, 3)}
Step-by-step explanation:
We know that:
R1 = {(1, 2), (2, 3), (3, 4)}
R2 = {(1, 1), (1, 2), (2, 1), (2, 2), (2, 3), (3, 1), (3, 2), (3, 3), (3, 4)}
Therefore, we get
a) R1 ∪ R2={(1, 1), (1, 2), (2, 1), (2, 2), (2, 3), (3, 1), (3, 2), (3, 3), (3, 4)}
b) R1 ∩ R2= {(1, 2), (2, 3), (3, 4)}
c) R1 – R2= ∅
d) R2 – R1= {(1, 1), (2, 1), (2, 2), (3, 1), (3, 2), (3, 3)}